A 17-kDa Fragment of Lactoferrin Associates With the Termination of Inflammation and Peptides Within Promote Resolution - Lutaty, Aviv; Soboh, Soaad; Schif-Zuck, Sagie; Zeituni-Timor, Orly; Rostoker, Ran; Podolska, Malgorzata; Herrmann, Martin; Munoz, Luis Enrique; Ariel, Amiram; Schauer, Christine (Frontiers in Immunology, 2018)
During the resolution of inflammation, macrophages engulf apoptotic polymorphonuclear cells (PMN) and can accumulate large numbers of their corpses. Here, we report that resolution phase macrophages acquire the neutrophil-derived glycoprotein lactoferrin (Lf) and fragments thereof in vivo and ex vivo. During the onset and resolving phases of inflammation in murine peritonitis and bovine mastitis, Lf fragments of 15 and 17 kDa occurred in various body fluids, and the murine fragmentation, accumulation, and release were mediated initially by neutrophils and later by efferocytic macrophages. The 17-kDa fragment contained two bioactive tripeptides, FKD and FKE that promoted resolution phase macrophage conversion to a pro-resolving phenotype. This resulted in a reduction in peritoneal macrophage numbers and an increase in the CD11b(low) subset of these cells. Moreover, FKE, but not FKD, peptides enhanced efferocytosis of apoptotic PMN, reduced TNF alpha and interleukin (IL)-6, and increased IL-10 secretion by lipopolysaccharide-stimulated macrophages ex vivo. In addition, FKE promoted neutrophil-mediated resolution at high concentrations (100 mu M) by enhancing the formation of cytokine-scavenging aggregated NETs (tophi) at a low cellular density. Thus, PMN Lf is processed, acquired, and "recycled" by neutrophils and macrophages during inflammation resolution to generate fragments and peptides with paramount pro-resolving activities.
EVALuna2:213271

Autoimmune, rheumatic, chronic inflammatory diseases: Neutrophil extracellular traps on parade - Podolska, Malgorzata; Mahajan, Aparna; Knopf, Jasmin; Hahn, Jonas; Boeltz, Sebastian; Munoz, Luis Enrique; Bilyy, Rostyslav; Herrmann, Martin (Autoimmunity, 2018)
Rheumatic diseases are a group of inflammatory conditions that affect joints and connective tissues and are often accompanied by pain and restriction of motility. In many of these diseases, autoantibodies develop that react with molecules/structures commonly found hidden in neutrophils. Neutrophil extracellular trap (NET) formation and release is considered a defense mechanism against pathogens or endogenous danger signals and it has been associated with initial inflammatory responses. NETs are also endowed with an important resolution potential based on its intrinsic enzymatic activity, but in the case they are not timely removed from the crime scene they might modulate subsequent immune responses and contribute to the pathogenesis of chronic inflammatory diseases. In this review, we will summarize the actual knowledge about the multifaceted roles of NETs in the etiology and pathogenesis of rheumatic autoimmune diseases.
EVALuna2:34670

Autoimmune, rheumatic, chronic inflammatory diseases: Neutrophil extracellular traps on parade - Podolska, Malgorzata; Mahajan, Aparna; Knopf, Jasmin; Hahn, Jonas; Boeltz, Sebastian; Munoz, Luis Enrique; Bilyy, Rostyslav; Herrmann, Martin (Autoimmunity Reviews, 2018)
Keywords: Neutrophil extracellular traps; rheumatic diseases; antiphospholipid syndrome; rheumatoid arthritis; systemic lupus erythematosus

Circulating Monocytes Serve as Novel Prognostic Biomarker in Pancreatic Ductal Adenocarcinoma Patients - Hansen, Frederik; David, Paul; Akram, Marina; Knoedler, Samuel; Mittelstädt, Anke; Merkel, Susanne; Podolska, Malgorzata; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; Kouhestani, Dina; Anthuber, Anna; et al. (Cancers, 2023)
Pancreatic ductal adenocarcinoma (PDAC) ranks among the most fatal cancer diseases, widely accepted to have the most dismal prognoses. Although immunotherapy has broadly revolutionized cancer treatment, its value in PDAC appears to be relatively low. Exhibiting protumoral effects, monocytes have recently been proposed as potential targets of such immunotherapeutic regimens. However, to date, the body of evidence on monocytes’ role in PDAC is scarce. Therefore, we analyzed monocytes in the peripheral blood of 58 PDAC patients prior to surgery and compared them to healthy individuals. PDAC patients showed increased levels of monocytes when compared to healthy controls In addition, patients with perineural infiltration demonstrated a higher percentage of monocytes compared to non-infiltrating tumors and PDAC G3 was associated with higher monocyte levels than PDAC G2. Patients with monocyte levels > 5% were found to have an 8.9-fold increased risk for a G3 and perineural infiltrated PDAC resulting in poorer survival compared to patients with <5% monocyte levels. Furthermore, PDAC patients showed increased expressions of CD86 and CD11c and decreased expressions of PD-L1 on monocytes compared to healthy individuals. Finally, levels of monocytes correlated positively with concentrations of IL-6 and TNF-α in plasma of PDAC patients. Based on our findings, we propose monocytes as a novel prognostic biomarker. Large-scale studies are needed to further decipher the role of monocytes in PDAC and investigate their potential as therapeutic targets.
CRIS-Team Scopus Importer:2023-02-03
Keywords: grading; liquid biopsy; monocytes; pancreatic ductal adenocarcinoma; perineural invasion; prognostic biomarker

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Experimental lupus is aggravated in mouse strains with impaired induction of neutrophil extracellular traps - Kienhofer, Deborah; Hahn, Jonas; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Urbonaviciute, Vilma; Johnsson, Caroline; Maueröder, Christian; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; Harrer, Thomas; et al. (JCI Insight, 2017)
Many effector mechanisms of neutrophils have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Neutrophil extracellular traps (NETs) have been assigned a particularly detrimental role. Here we investigated the functional impact of neutrophils and NETs on a mouse model of lupus triggered by intraperitoneal injection of the cell death-inducing alkane pristane. Pristane-induced lupus (PIL) was aggravated in 2 mouse strains with impaired induction of NET formation, i.e., NOX2-deficient (Ncf1-mutated) and peptidyl arginine deiminase 4-deficient (PAD4-deficient) mice, as seen from elevated levels of antinuclear autoantibodies (ANAs) and exacerbated glomerulonephritis. We observed a dramatically reduced ability to form pristane-induced NETs in vivo in both Ncf1-mutated and PAD4-deficient mice, accompanied by higher levels of inflammatory mediators in the peritoneum. Similarly, neutropenic Mcl-1ΔMyelo mice exhibited higher levels of ANAs, which indicates a regulatory function in lupus of NETs and neutrophils. Blood neutrophils from Ncf1-mutated and human individuals with SLE exhibited exuberant spontaneous NET formation. Treatment with specific chemical NOX2 activators induced NET formation and ameliorated PIL. Our findings suggest that aberrant NET is one of the factors promoting experimental lupus-like autoimmunity by uncontrolled release of inflammatory mediators.
EVALuna2:1833

Frontline Science: Aggregated neutrophil extracellular traps prevent inflammation on the neutrophil-rich ocular surface - Mahajan, Aparna; Grüneboom, Anika; Petru, Lenka; Podolska, Malgorzata; Kling, Lasse; Maueröder, Christian; Dahms, Florian; Christiansen, Silke; Günter, Lochnit; Krenn, Veit; Jünemann, Anselm; Bock, Felix; et al. (Journal of Leukocyte Biology, 2019)
Eye rheum is a physiological discharge, which accumulates at the medial angle of the healthy eye soon after opening in the morning. Microscopic evaluation of eye rheum revealed the presence of viable neutrophils, bacteria, epithelial cells, and particles, aggregated by neutrophil extracellular traps. We observed that in the evening, during eye closure, high C5a recruited neutrophils to the tear film and activated them. In this hypoxic area rich in CO 2 , neutrophils fight microbial aggressors by degranulation. Immediately after eye opening, the microenvironment of the ocular surface changes, the milieu gets normoxic, and loss of CO 2 induces subtle alkalinization of tear film. These conditions favored the formation of neutrophil extracellular traps (NETs) that initially covers the ocular surface and tend to aggregate by eyelid blinking. These aggregated neutrophil extracellular traps (aggNETs) are known as eye rheum and contain several viable neutrophils, epithelial cells, dust particles, and crystals packed together by NETs. Similar to aggNETs induced by monosodium urate crystals, the eye rheum shows a robust proteolytic activity that degraded inflammatory mediators before clinically overt inflammation occur. Finally, the eye rheum passively floats with the tear flow to the medial angle of the eye for disposal. We conclude that the aggNETs-based eye rheum promotes cleaning of the ocular surface and ameliorates the inflammation on the neutrophil-rich ocular surfaces.
CRIS-Team Scopus Importer:2019-05-02
Keywords: degranulation; eye rheum; inflammation; NETs; neutrophils; resolution; serine protease

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Graphene Oxide Nanosheets for Localized Hyperthermia-Physicochemical Characterization, Biocompatibility, and Induction of Tumor Cell Death - Podolska, Malgorzata; Barras, Alexandre; Alexiou, Christoph; Frey, Benjamin; Gaipl, Udo; Boukherroub, Rabah; Szunerits, Sabine; Janko, Christina; Munoz, Luis Enrique (Cells, 2020)
Background: The main goals of cancer treatment are not only to eradicate the tumor itself but also to elicit a specific immune response that overcomes the resistance of tumor cells against chemo- and radiotherapies. Hyperthermia was demonstrated to chemo- and radio-sensitize cancerous cells. Many reports have confirmed the immunostimulatory effect of such multi-modal routines. Methods: We evaluated the interaction of graphene oxide (GO) nanosheets; its derivatives reduced GO and PEGylated rGO, with components of peripheral blood and evaluated its thermal conductivity to induce cell death by localized hyperthermia. Results: We confirmed the sterility and biocompatibility of the graphene nanomaterials and demonstrated that hyperthermia applied alone or in the combination with radiotherapy induced much more cell death in tumor cells than irradiation alone. Cell death was confirmed by the release of lactate dehydrogenase from dead and dying tumor cells. Conclusion: Biocompatible GO and its derivatives can be successfully used in graphene-induced hyperthermia to elicit tumor cell death.
CRIS-Team WoS Importer:2020-05-15

Guidelines for the use of flow cytometry and cell sorting in immunological studies - Cossarizza, Andrea; Chang, Hyun-Dong; Radbruch, Andreas; Akdis, Mubeccel; Andrae, Immanuel; Annunziato, Francesco; Bacher, Petra; Barnaba, Vincenzo; Battistini, Luca; Bauer, Wolfgang M.; Baumgart, Sabine; Becher, Burkhard; et al. (European Journal of Immunology, 2017)
EVALuna2:13453

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

IL-3: key orchestrator of inflammation - Podolska, Malgorzata; Grützmann, Robert; Pilarsky, Christian; Benard, Alan (Frontiers in Immunology, 2024)
Interleukin (IL)-3 has long been known for its hematopoietic properties. However, recent evidence has expanded our understanding of IL-3 function by identifying IL-3 as a critical orchestrator of inflammation in a wide array of diseases. Depending on the type of disease, the course of inflammation, the cell or the tissue involved, IL-3 promotes either pathologic inflammation or its resolution. Here, we describe the cell-specific functions of IL-3 and summarize its role in diseases. We discuss the current treatments targeting IL-3 or its receptor, and highlight the potential and the limitations of targeting IL-3 in clinics.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cancer; CD123; infection; inflammation; interleukin-3

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

Neutrophil Extracellular Traps Initiate Gallstone Formation - Munoz, Luis Enrique; Boeltz, Sebastian; Bilyy, Rostyslav; Schauer, Christine; Mahajan, Aparna; Widulin, Navena; Grüneboom, Anika; Herrmann, Irmgard; Boada, Edgyda; Rauh, Manfred; Krenn, Veit; Biermann, Mona H.C.; et al. (Immunity, 2019)
The presence of gallstones (cholelithiasis) is a highly prevalent and severe disease and one of the leading causes of hospital admissions worldwide. Due to its substantial health impact, we investigated the biological mechanisms that lead to the formation and growth of gallstones. We show that gallstone assembly essentially requires neutrophil extracellular traps (NETs). We found consistent evidence for the presence of NETs in human and murine gallstones and describe an immune-mediated process requiring activation of the innate immune system for the formation and growth of gallstones. Targeting NET formation via inhibition of peptidyl arginine deiminase type 4 or abrogation of reactive oxygen species (ROS) production, as well as damping of neutrophils by metoprolol, effectively inhibit gallstone formation in vivo. Our results show that after the physicochemical process of crystal formation, NETs foster their assembly into larger aggregates and finally gallstones. These insights provide a feasible therapeutic concept to prevent cholelithiasis in patients at risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: calcium carbonate crystals; cholesterol crystals; gallstone growth; gallstones; lisosomal leakage; lithogenic diet; neutrophil extracellular traps; neutrophils; NOX2; PADi4

Oxidative Burst-Dependent NETosis Is Implicated in the Resolution of Necrosis-Associated Sterile Inflammation - Biermann, Mona H. C.; Podolska, Malgorzata; Knopf, Jasmin; Reinwald, Christiane; Weidner, Daniela; Maueröder, Christian; Hahn, Jonas; Kienhoefer, Deborah; Barras, Alexandre; Boukherroub, Rabah; Szunerits, Sabine; Bilyy, Rostyslav; et al. (Frontiers in Immunology, 2016)
Necrosis is associated with a profound inflammatory response. The regulation of necrosis-associated inflammation, particularly the mechanisms responsible for resolution of inflammation is incompletely characterized. Nanoparticles are known to induce plasma membrane damage and necrosis followed by sterile inflammation. We observed that injection of metabolically inert nanodiamonds resulted in paw edema in WT and Ncf1** mice. However, while inflammation quickly resolved in WT mice, it persisted over several weeks in Ncf1** mice indicating failure of resolution of inflammation. Mechanistically, NOX2-dependent reactive oxygen species (ROS) production and formation of neutrophil extracellular traps were essential for the resolution of necrosis-induced inflammation: hence, by evaluating the fate of the particles at the site of inflammation, we observed that Ncf1** mice deficient in NADPH-dependent ROS failed to generate granulation tissue therefore being unable to trap the nanodiamonds. These data suggest that NOX2-dependent NETosis is crucial for preventing the chronification of the inflammatory response to tissue necrosis by forming NETosis-dependent barriers between the necrotic and healthy surrounding tissue.
EVALuna2:13386

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

ROS is the boss - Hahn, Jonas; Kienhofer, Deborah; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Maueröder, Christian; Urbonaviciute, Vilma; Munoz, Luis Enrique; Hultqvist, Malin; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; et al. (2017)
EVALuna2:13467

Sweet but dangerous - the role of immunoglobulin G glycosylation in autoimmunity and inflammation - Biermann, Mona; Griffante, G.; Podolska, Malgorzata; Boeltz, Sebastian; Stürmer, Jörg; Munoz, Luis Enrique; Bilyy, R.; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2016)
Glycosylation is well-known to modulate the functional capabilities of immunoglobulin G (IgG)-mediated cellular and humoral responses. Indeed, highly sialylated and desialylated IgG is endowed with anti- and pro-inflammatory activities, respectively, whereas fully deglycosylated IgG is a rather lame duck, with no effector function besides toxin neutralization. Recently, several studies revealed the impact of different glycosylation patterns on the Fc part and Fab fragment of IgG in several autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Here, we provide a synoptic update summarizing the most important aspects of antibody glycosylation, and the current progress in this field. We also discuss the therapeutic options generated by the modification of the glycosylation of IgG in a potential treatment for chronic inflammatory diseases.
EVALuna2:13284

Treatment with DNases rescues hidden neutrophil elastase from aggregated NETs - Podolska, Malgorzata; Mahajan, Aparna; Hahn, Jonas; Knopf, Jasmin; Maueröder, Christian; Petru, Lenka; Ullmann, Marc; Schett, Georg; Leppkes, Moritz; Herrmann, Martin; Munoz, Luis Enrique; Schauer, Christine (Journal of Leukocyte Biology, 2019)
The release of neutrophil extracellular traps (NETs) is one of the weapons neutrophils have in their armory. NETs consist of extracellular chromatin fibers decorated with a plethora of cytoplasmic and granular proteins, such as the antimicrobial serine protease neutrophil elastase (NE). Because the first description of NETs as beneficial to the host, reports on their double-faced role in health and disease have considerably increased recently. On one hand, NETs reportedly trap and kill bacteria and also participate in the resolution of the acute inflammation associated with infection and with tissue damage. On the other hand, numerous negative aspects of NETs contribute to the etiopathogenesis of autoimmune disorders. Employing soluble and solid fluorescent substrates, we demonstrate the interaction of NE with aggregated NETs (aggNETs), the limitation of its enzymatic activity and the containment of the enzyme from surrounding tissues. These events prevent the spread of inflammation and tissue damage. The detection of DNase 1-dependent elevation of NE activity attests the continuous presence of patrolling neutrophils forming NETs and aggNETs even under conditions physiologic conditions.
CRIS-Team Scopus Importer:2019-09-17
Keywords: aggregated NETs; DNase 1; NETs; neutrophil elastase; neutrophils

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment